Synthesis, antimycobacterial activity and influence on mycobacterial InhA and PknB of 12-membered cyclodepsipeptides. Issue 12 (23rd July 2018) - Laqua, Katja; Klemm, Marcel; Richard-Greenblatt, Melissa; Richter, Adrian; Liebe, Linda; Huang, Tingting; Lin, Shuangjun; Guardia, Ana; Pérez-Herran, Esther; Ballell, Lluís; Av-Gay, Yossef; Imming, Peter
Graphical abstract: Abstract: In recent years, several small natural cyclopeptides and cyclodepsipeptides were reported to have antimycobacterial activity. Following this lead, a synthetic pathway was developed for a small series of 12-membered ring compounds with one amide and two ester bonds (cyclotridepsipeptides). Within the series, the ring system proved to be necessary for growth inhibition of Mycobacterium smegmatis and Mycobacterium tuberculosis in the low micromolar range. Open-chain precursors and analogues were inactive. The compounds modulated autophosphorylation of the mycobacterial protein kinase B (PknB). PknB inhibitors were active at µM concentration against mycobacteria while inducers were inactive. PknB regulates the activity of the mycobacterial reductase InhA, the target of isoniazid. The activity of the series against Mycobacterium bovis BCG InhA overexpressing strains was indistinguishable from that of the parental strain suggesting that they do not inhibit InhA. All substances were not cytotoxic (HeLa > 5 µg/ml) and did not show any significant antiproliferative effect (HUVEC > 5 µg/ml; K-562 > 5 µg/ml). Within the scope of this study, the molecular target of this new type of small cyclodepsipeptide was not identified, but the data suggest interaction with PknB or other kinases may partly cause the activity.